Implementasi Pendidikan Karakter oleh Guru Biologi SMA Negeri di Kabupaten Muara Enim - Atira Elpariska Maya; Siti Huzaifah; Kodri Madang (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2017)
This research aims to describe the understanding, implementation and difficulties faced by Biology teachers of State Senior High School in Muara Enim district about character education. The research subjects consisted of three biology teachers which determined by purposive sampling technique. Data collection using interview techniques, audiovisual materials and documents it is analyzed by transcription, coding and verification of data. The results showed by three aspects that are: 1) Understanding Biology teacher of State Senior High School in Muara Enim Regency about character education is an effort to instill character through habituation and exemplary to form a good attitude of students. Character education consists of 18 values. Biology teacher plans character education by identifying the value of character education that will be implanted. Learning implementation conducted according to the lesson plan. Then, to measure student’s character abilities the teacher using character measurement instrument sheet with a character assessment section. 2) Implementation of character education by Biology teachers of State Senior High School in Muara Enim Regency consist of planning and implementation aspect. Values designed and implemented by teachers Biology consists of discipline, curiosity, joy of reading, and responsibility. Value that is designed but not implemented is discipline, creative value, curiosity value, and joy of reading. Value that is not designed but implemented is discipline, hard work, joy of reading, and responsibility. General, Biology teachers carry out the value of character education through the use of words and have not utilized the learning materials to develop the value. 3) The difficulties encountered that is facing by Biology teachers include identifying the value of character education and performing individual character assessments.Keywords : Implementation, Character Education, Biology Teacher